2022
DOI: 10.35378/gujs.844650
|View full text |Cite
|
Sign up to set email alerts
|

A Logistics Model Suggestion for A Logistics Centre to Be Established: An Application in Aegean and Central Anatolia Region

Abstract: Highlights• This paper focuses on selecting the optimum location for a logistics center to be established.• An integrated logistics model is proposed for the efficient and useful logistics center.• The results of the proposed logistics model are similar for the industrial and logistics sectors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Plateaus, wide plains, and meadows are more common in the west part of the basin. The Hirfanli Dam, which was built on the Kizilirmak River in 1959 for flood control and hydropower purposes, has a surface area of 263 km 2 and reservoir volume of 5,980 hm 3 at normal water surface level [22][23][24].…”
Section: Study Area and Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Plateaus, wide plains, and meadows are more common in the west part of the basin. The Hirfanli Dam, which was built on the Kizilirmak River in 1959 for flood control and hydropower purposes, has a surface area of 263 km 2 and reservoir volume of 5,980 hm 3 at normal water surface level [22][23][24].…”
Section: Study Area and Datamentioning
confidence: 99%
“…Dev., Variation, Skewness and Kurtsosis) of temperature records between 1965 and 2017 are shown in Table 1. The graphs of the temperature series for each station in the Hirfanli Dam Basin are given in Figure 2 The mean temperature is around 10.02°C and also the annual temperature decreases from the upstream to the downstream due to the increase in altitude (Figure 3) [23].…”
Section: Study Area and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, Hirfanli Dam basin, which is located in the semi-arid climate region where climate change can be seen due to its location, was chosen as the study area. The drought situation in the basin and the Central Anatolia region, where it is geographically located, has been examined with different methods in the literature [37][38][39][40][41][42]. Temperature and precipitation series analyzes were made by using Mann Kendall (MK), Spearman's Rho (SR) and Innovative Trend Analysis (ITA).…”
Section: Introductionmentioning
confidence: 99%
“…Bacanli, Dikbas, and Baran (2011 reported that the Central Anatolian region was in danger of severe drought. Yıldız (2014) reported that the Central Anatolian Region was under the influence of high-frequency droughts in the 1953-2004 period. Arslan (2017), who examined the drought of Niğde between 1950 and 2015, reported that there was an increase in humidity.…”
Section: Introductionmentioning
confidence: 99%